Self-emulsifying borate ester wax composite water-resistant emulsion, super-hydrophobic coating and preparation method thereof, and super-hydrophobic paper
Patent Information
- Application Number
- CN202611090778.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-07-22
AI Technical Summary
[0003]然而,与塑料相比,纸张的强度,尤其是湿强度是制约一些特殊场合应用最核心的问题
[0043](1)本发明采用自乳化技术,依靠硼酸酯蜡的自乳化作用,无需外加乳化剂,制备过程绿色、环保、工艺简单。
Smart Images

Figure CN122588912B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of chemical and papermaking chemical technology, specifically relating to a self-emulsifying borate ester wax composite water-resistant emulsion, a superhydrophobic coating and its preparation method, and a superhydrophobic paper. Background Technology
[0002] In recent years, with the continuous enhancement of global environmental awareness, the concept of replacing plastic with paper has gradually emerged, and specialty papers such as mulch film paper and superhydrophobic packaging paper have also gradually developed. Replacing plastic with paper uses fiber as the main raw material, and modifies it through internal additives or surface coating to give it high water resistance and high barrier properties, thereby narrowing the performance gap between paper and plastic.
[0003] However, compared to plastics, the strength of paper, especially its wet strength, is the most critical issue limiting its application in certain special situations. The fibers readily absorb water, disrupting the hydrogen bonds between the hydroxyl groups, reducing strength, and making the paper prone to stretching, tearing, or breaking. Current technologies often employ fluorocarbon compounds or organosilicon substances for surface hydrophobic modification, but these methods suffer from high costs, complex processes, and environmental unfriendliness.
[0004] Therefore, how to improve the water resistance and wet strength of paper in a green and efficient manner, especially the tensile strength in special situations, has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a self-emulsifying borate ester wax composite water-resistant emulsion, a superhydrophobic coating, its preparation method, and a superhydrophobic paper. This invention is based on the self-emulsifying effect of borate ester wax, eliminating the need for external emulsifiers. The preparation process is green, environmentally friendly, and simple.
[0006] The technical solution adopted in this invention is as follows:
[0007] In a first aspect, the present invention provides a method for preparing a self-emulsifying borate ester wax composite water-resistant emulsion, the method comprising the following steps:
[0008] Borate ester wax and 3-(trimethoxysilyl)propyl methacrylate (MPS) are mixed, heated to 80-85℃, and water preheated to the same temperature is added. After high-shear emulsification treatment, the mixture is cooled to room temperature to obtain a self-emulsifying borate ester wax composite water-resistant emulsion.
[0009] The borate ester wax comprises a compound having the following general formula: B(OR1)(OR2)(OR3);
[0010] R1, R2, and R3 are each independently selected from the following groups:
[0011] (a)-CH2CH2NH-(CH2CH2O)n -H;
[0012] (b) -CH2CH(OH)CH2OH or -CH2CH(OCOR x CH2OCOR y ;
[0013] (c) -CH2CH(OH)CH3 or -CH2CH(OCOR) z CH3;
[0014] Among them, R x R y R z Each is independently selected from H or -COC. 25 H 51 ;
[0015] n = 0.32 - 6.03;
[0016] And at least one of R1, R2, and R3 is selected from (a), at least one is selected from (b), and at least one is selected from (c).
[0017] Note: n is the average number of repeating units. When n = 0.32, it means that each borate wax molecule has an average of 0.32 ethylene oxide units attached. By adjusting the amount of ethylene oxide, borate wax products with different n values can be obtained.
[0018] For example, the borate ester wax may have the following structure I (this structure is only a representative example, and the actual product is a mixture):
[0019]
[0020] It should be noted that Structure I above is only used to indicate the type and linkage of functional groups contained in the borate ester wax of the present invention. Since the three hydroxyl groups of boric acid have the same chemical reactivity, the linkage of substituents is random when reacting with ethylene glycolamine, glycerol, and propylene glycol. Therefore, the actual product is a mixture containing various borate ester compounds with different structures. This mixture has the technical effects described in the present invention.
[0021] Furthermore, the borate ester wax is prepared by the following method:
[0022] Boric acid, ethylene glycolamine, glycerol, and propylene glycol are reacted in a molar ratio of 1:(0.5-1.5):(0.5-1.5):(0.5-1.5) to obtain a borate ester skeleton; the borate ester skeleton is then reacted with wax acid in a molar ratio of 1:(0.5-1.5); ethylene oxide is then added to make the molar ratio of ethylene oxide to the initial boric acid 0.5-13:1, and after the reaction, a borate ester wax with an average degree of polymerization n=0.32-6.03 is obtained.
[0023] The specific steps are as follows: Boric acid, ethylene glycolamine, glycerol, and propylene glycol are added to methanol solvent. The initial temperature is raised to 80-100℃ for pre-reaction to remove some water. The temperature is then raised to 160-180℃ for the main reaction, maintained for 4-6 hours to ensure complete formation of the borate ester bond. Sodium carbonate is added during the reaction to prevent hydrolysis of the borate ester bond. Tetrabutylammonium bromide (TBAB) is used to increase the reaction rate. After the reaction, the obtained product is mixed with wax acid, dissolved in toluene, heated to 130-150℃, and p-toluenesulfonic acid is added as a catalyst. The reaction is carried out for 5 hours, and the resulting product is precipitated and washed. The product is added to a high-temperature, high-pressure reactor, sodium hydroxide is added as a catalyst, the temperature is raised to 80-120℃, the reactor pressure is controlled at 0.2-0.5 MPa, ethylene oxide is introduced, and the reaction is carried out for 2-4 hours to obtain the final product - borate ester wax.
[0024] Furthermore, the mass ratio of 3-(trimethoxysilyl)methacrylate to borate wax is 5-10:60-95; the mass ratio of water to the total mass of the above materials is 4:1-2.4:1.
[0025] Furthermore, the method also incorporates insect wax.
[0026] Furthermore, the mass ratio of the insect wax, 3-(trimethoxysilyl)methacrylate, and borate ester wax is 0.1-30:5-10:60-95; the mass ratio of water to the total mass of the insect wax, 3-(trimethoxysilyl)methacrylate, and borate ester wax is 4:1-2.4:1.
[0027] Furthermore, the high-shear emulsification process includes: first shearing at 4000-4500 r / min for 1-2 minutes, and then shearing at 11000-12000 r / min for 20-30 minutes.
[0028] In this invention, the borate ester wax comprises a hexadecyl carbon chain, an amino group, and a polyoxyethylene chain. The hexadecyl carbon chain is structurally similar to that of insect wax, exhibiting good compatibility and improving emulsion stability. Simultaneously, this long-chain alkyl group possesses water-resistant properties, reducing or even replacing the use of insect wax. The amino group endows the borate ester wax with emulsifying and coupling functions, allowing it to adsorb onto the surface of solid particles and enhance interfacial bonding. The polyoxyethylene chain is the primary emulsifying group; by adjusting its degree of polymerization n (n = 0.32-6.03), an HLB value of 12-16 can be achieved, thereby obtaining suitable self-emulsifying properties.
[0029] In this invention, insect wax, borate ester wax, and subsequently polymerized poly-3-(trimethoxysilyl)propyl methacrylate work together to provide water resistance; borate ester wax and insect wax also possess good lubricating properties, enabling the emulsion and superhydrophobic coating to maintain the interfacial lubrication characteristics and stability. Organic borate ester wax is used as a coupling agent and dispersant in the coating preparation process.
[0030] The present invention also provides a self-emulsifying borate ester wax composite water-resistant emulsion prepared by the above method.
[0031] Secondly, the present invention provides a method for preparing a superhydrophobic coating, the method comprising the following steps:
[0032] Water, nano-silica, nano-wollastonite, micron-sized shell powder, nano-cellulose, and the self-emulsifying borate ester wax composite water-resistant emulsion described in the first aspect are mixed, dispersed and ground, heated to 85-90℃, and an initiator solution is added to carry out a polymerization reaction. After the reaction is completed, the mixture is sheared and ultrasonically dispersed to obtain a superhydrophobic coating.
[0033] Furthermore, the mass ratio of water, nano-silica, nano-wollastonite, micron-sized shell powder, and nano-cellulose is 50:5-10:5-10:30-40:1-2; wherein, the shell powder is oyster shell powder, which is obtained by crushing, enzymatic removal of protein, washing with water, and ball milling to obtain 5-40 micron shell powder; the mass ratio of the self-emulsifying borate ester wax composite water-resistant emulsion to the total mass ratio of water, nano-silica, nano-wollastonite, micron-sized shell powder, and nano-cellulose is 2-5:1.
[0034] Furthermore, the dispersion and grinding process takes 50-70 minutes.
[0035] Further, the initiator solution is a mixed solution of ammonium persulfate and sodium bisulfite, with a mass ratio of ammonium persulfate to sodium bisulfite of (1-2):(1-2). The total mass concentration of the solute in the initiator solution is 1-5‰, and the solute is ammonium persulfate and sodium bisulfite. The amount of the initiator solution used, based on the total mass of the solute, is 0.2-0.5% of the mass of propyl 3-(trimethoxysilyl)methacrylate.
[0036] Furthermore, the polymerization reaction takes 2-4 hours.
[0037] Furthermore, after the reaction is complete and cooled, it is subjected to high shear for 20-40 minutes, followed by ultrasonic dispersion for 5-15 minutes.
[0038] The present invention also provides a superhydrophobic coating prepared by the above method.
[0039] Thirdly, the present invention provides a method for preparing superhydrophobic paper, the method comprising the following steps: coating the superhydrophobic coating onto the surface of the base paper, with a coating amount of 6-12 g / m². 2 Dry until the moisture content is below 7%, then hot press for 2-8 minutes to obtain superhydrophobic paper.
[0040] Furthermore, the base paper is mulch film base paper.
[0041] The present invention also provides superhydrophobic paper prepared by the above method.
[0042] Compared with the related technologies known to the inventors, one of the technical solutions of the present invention has the following beneficial effects:
[0043] (1) The present invention adopts self-emulsification technology, relying on the self-emulsification effect of borate ester wax, without the need for external emulsifiers, and the preparation process is green, environmentally friendly and simple.
[0044] After preparing a stable coating, this invention further initiates polymerization reactions at the liquid / solid interface and the liquid / liquid interface, causing MPS to form a polymer network on the surface of inorganic particles and emulsion droplets, thereby "anchoring" the components together and further improving the water resistance and storage stability of the coating.
[0045] (2) The superhydrophobic paper prepared by the present invention has high dry and wet strength, superhydrophobicity (contact angle ≥155°), water can be washed away, and it can effectively prevent paper breakage and tearing caused by water penetration.
[0046] (3) The superhydrophobic paper prepared by this invention has excellent water vapor blocking properties (below 51 g·m). -2 24h -1 It has good moisturizing properties and is suitable for special occasions such as mulch film and cold storage paper. Attached Figure Description
[0047] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0048] Figure 1 Infrared spectrum of the borate ester wax prepared in Example 1.
[0049] Figure 2 High performance liquid chromatography (HPLC) chromatogram of the borate ester wax prepared in Example 1.
[0050] Figure 3 The contact angle test comparison diagram shows that A is the contact angle photo of the uncoated base paper and B is the contact angle photo of the superhydrophobic paper prepared in Example 1.
[0051] Figure 4 SEM images, where A is the surface morphology of the uncoated paper and B is the surface morphology of the paper after coating with the superhydrophobic coating prepared in Example 1. Detailed Implementation
[0052] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0053] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments of the present invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, and / or combinations thereof.
[0054] This invention uses fiber-based base paper as a matrix and coats its surface with a superhydrophobic coating to prepare superhydrophobic paper for use in humid environments. Because the superhydrophobic layer effectively prevents liquids from spreading on the fiber surface, it acts as a self-cleaning agent, preventing water from penetrating into the paper. When used in cold storage, water vapor cannot penetrate the paper. When used as mulch film, irrigation water will not penetrate, thus not affecting the strength of the mulch film. This technology provides technical support and guidance for the preparation of superhydrophobic coatings and their application in special paper types.
[0055] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0056] Example 1 (corresponding to n=0.32)
[0057] I. Synthesis of Boronate Waxes
[0058] 1 mol of boric acid, 1 mol of ethylene glycolamine, 1 mol of glycerol, and 1 mol of propylene glycol were added to 200 mL of methanol. The mixture was initially heated to 90 °C for a pre-reaction to remove some water. The temperature was then increased to 170 °C for the main reaction, which was maintained for 5 hours to ensure complete formation of the borate ester bonds. A small amount of 3 g of sodium carbonate was added during the reaction to prevent hydrolysis of the borate ester bonds. 0.03 mol of tetrabutylammonium bromide (TBAB) was used to increase the reaction rate. After the reaction, the resulting product was mixed with 1 mol of waxy acid and dissolved in 100 mL of toluene. The mixture was heated to 140 °C, and 0.01 mol of p-toluenesulfonic acid was added as a catalyst. The reaction was continued for 5 hours, and the resulting product was precipitated and washed. The product was then added to a high-temperature, high-pressure reactor, and 0.01 mol of sodium hydroxide was added as a catalyst. The temperature was increased to 100 °C, the reactor pressure was controlled at 0.4 MPa, and 0.64 mol of ethylene oxide was introduced. The reaction was continued for 3 hours to obtain the final product.
[0059] The infrared spectrum of the borate wax prepared in this embodiment is as follows: Figure 1 As shown. By Figure 1 It can be seen that at 2850cm -1 A strong absorption peak appears at 1350 and 1045 cm⁻¹, corresponding to the CH stretching vibration of long-chain alkyl groups; -1 The characteristic absorption peak appears at 1100 cm⁻¹, which is attributed to the stretching vibration of the boronic ester bond (BO); -1 The absorption peak at 1725 cm⁻¹ is attributed to the COC stretching vibration of the polyethylene oxide chain; the absorption peak at 1725 cm⁻¹ is attributed to the COC stretching vibration of the polyethylene oxide chain. -1 The absorption peaks observed at [location] are attributed to the stretching vibrations of the ester bond (C=O). Infrared spectroscopy analysis indicates that the target borate ester wax product was successfully synthesized in this embodiment.
[0060] The borate ester wax prepared in this embodiment was analyzed by high performance liquid chromatography (detection wavelength 210 nm), and its chromatogram is shown below. Figure 2 As shown in the figure. The results indicate that the obtained product is a mixture of multiple components, with a main peak retention time of 4.312 min and a peak area ratio of approximately 40.8%.
[0061] II. Preparation of Self-Emulsifying Borate Acid Ester Wax Composite Water-Repellent Emulsion
[0062] Add 5g of 3-(trimethoxysilyl)propyl methacrylate and 95g of borate wax (n=0.32) to an emulsifying kettle and heat to 80-85℃. Preheat 400g of water to 80-85℃.
[0063] Turn on high shear, increase the speed to 4000-4500 r / min, slowly add a small amount of water, and shear and stir for 1 minute; then increase the speed to 11000-12000 r / min, slowly add the remaining water to the emulsification tank, shear at high speed for 20-30 minutes, and quickly cool to room temperature to obtain a self-emulsifying borate ester wax composite water-resistant emulsion.
[0064] III. Preparation of Superhydrophobic Coatings
[0065] Add 50g water, 5g nano silica, 5g nano wollastonite, 30g micron-sized shell powder (oyster shell powder, which is crushed, enzyme-removed for protein, washed with water, and ball-milled to 5-40 microns), and 1g nanocellulose to a high-speed dispersion vessel. Turn on the stirring and slowly stir until uniform. Then add 200g of the above self-emulsifying borate ester wax composite water-resistant emulsion and disperse and grind at high speed for 50 minutes.
[0066] The coating was heated to 85°C, and a pre-dissolved solution of ammonium persulfate and sodium bisulfite (0.006g ammonium persulfate and 0.006g sodium bisulfite dissolved in 6g water) was added dropwise over 10 minutes. The mixture was stirred and reacted for 3 hours. After cooling, the reactants were further subjected to high shear in a high-speed dispersion vessel for 30 minutes, followed by ultrasonic dispersion for 10 minutes. The mixture was then discharged to obtain the superhydrophobic coating.
[0067] IV. Preparation of Superhydrophobic Paper
[0068] The above-mentioned superhydrophobic coating was applied to the surface of the base paper, with the coating amount controlled at 6 g / m². 2 After the paper is dried, the moisture content is controlled to be below 7%, and then it is hot-pressed for 5 minutes to melt and spread the anti-water wax emulsion on the surface, forming a rough superhydrophobic surface with nano and micro structure, thus obtaining superhydrophobic paper.
[0069] Figure 3 This is a comparison diagram of the contact angles of the superhydrophobic paper prepared in this embodiment and the uncoated base paper. Figure 3 As can be seen in diagram A, water droplets on the uncoated paper spread rapidly, with a contact angle much less than 90°, indicating hydrophilicity; Figure 3 As can be seen from Figure B, after applying the superhydrophobic coating of Example 1 of this invention, the water droplets are perfectly spherical with a contact angle of 156°, indicating that the paper has excellent superhydrophobic properties.
[0070] Figure 4 SEM comparison images of the superhydrophobic paper prepared for this example and the uncoated base paper. Figure 4 As can be seen in Figure A, the fiber surface of the uncoated base paper is relatively smooth, without any obvious rough structure. Figure 4As can be seen from Figure B, after the superhydrophobic coating is applied, nano-silica, nano-wollastonite, and micron-sized shell powder are evenly distributed on the fiber surface and between the fibers, forming a micron-nano composite rough structure, which provides the necessary surface morphology basis for the realization of superhydrophobic properties.
[0071] Example 2 (corresponding to n=3)
[0072] I. Synthesis of Boronate Waxes
[0073] Following the synthesis steps of Example 1, the amount of ethylene oxide was adjusted to 6 mol, and n=3 was controlled. The remaining raw material ratios and reaction conditions were the same as in Example 1.
[0074] II. Preparation of Self-Emulsifying Borate Acid Ester Wax Composite Water-Repellent Emulsion
[0075] Add 15g of insect wax (commercially available), 8g of 3-(trimethoxysilyl)propyl methacrylate, and 77g of borate wax (n=3) to an emulsifying kettle and heat to 85℃. Preheat 300g of water to 80-85℃.
[0076] The remaining operations are the same as in Example 1.
[0077] III. Preparation of Superhydrophobic Coatings
[0078] Add 50g water, 8g nano silica, 8g nano wollastonite, 35g micron-sized shell powder (oyster shell powder, which is crushed, enzyme-removed for protein, washed with water, and ball-milled to 5-40 microns), and 1.5g nanocellulose to a high-speed dispersion vessel, stir evenly, add 300g of the above self-emulsifying borate ester wax composite water-resistant emulsion, and disperse and grind at high speed for 60 minutes.
[0079] The above coating was heated to 88°C, and a solution of ammonium persulfate and sodium bisulfite (0.024g + 0.024g, dissolved in 12g water) was added dropwise. The reaction was carried out for 3 hours. After cooling, the material obtained from the reaction was further subjected to high shear for 30 minutes and ultrasonication for 10 minutes in a high-speed dispersion vessel before being discharged.
[0080] IV. Preparation of Superhydrophobic Paper
[0081] The coating amount is 10 g / m², and the rest is the same as in Example 1.
[0082] Example 3 (corresponding to n=6.03)
[0083] I. Synthesis of Boronate Waxes
[0084] Following the synthesis steps of Example 1, the amount of ethylene oxide was adjusted to 12.06 mol, and n=6.03 was controlled. The remaining raw material ratios and reaction conditions were the same as in Example 1.
[0085] II. Preparation of Self-Emulsifying Borate Acid Ester Wax Composite Water-Repellent Emulsion
[0086] Add 30g of insect wax (commercially available), 10g of 3-(trimethoxysilyl)propyl methacrylate, and 60g of borate wax (n=6.03) to an emulsifying kettle and heat to 85℃. Preheat 240g of water to 80-85℃.
[0087] The remaining operations are the same as in Example 1.
[0088] III. Preparation of Superhydrophobic Coatings
[0089] Add 50g water, 5g nano silica, 5g nano wollastonite, 40g micron-sized shell powder, and 2g nano cellulose to a high-speed dispersion vessel, stir slowly until homogeneous, add 500g of the above self-emulsifying borate ester wax composite water-resistant emulsion, and disperse and grind at high speed for 70 minutes.
[0090] The above coating was heated to 90°C, and a solution of ammonium persulfate and sodium bisulfite (0.034g + 0.034g, dissolved in 6.8g water) was added dropwise over 10 minutes. The mixture was stirred and reacted for 3 hours. After cooling, the resulting material was further subjected to high shear in a high-speed dispersion vessel for 30 minutes, followed by ultrasonic dispersion for 10 minutes, and then discharged.
[0091] IV. Preparation of Superhydrophobic Paper
[0092] The coating amount was 12 g / m², and the rest was the same as in Example 1.
[0093] Comparative Example 1 (using only borate wax, without insect wax and MPS)
[0094] I. Preparation of Self-Emulsifying Borate Wax Composite Water-Repellent Emulsion
[0095] Add 95g of borate wax (n=0.32) to the emulsification vessel and heat to 80-85℃. Preheat 400g of water to 80-85℃.
[0096] Turn on high shear, increase the speed to 4000-4500 rpm, slowly add a small amount of water, shear and stir for 1 minute, then increase the speed to between 11000-12000 rpm, slowly add the remaining water to the emulsification tank, shear at high speed for 20-30 minutes, and quickly cool to room temperature for later use.
[0097] II. Preparation of Coatings
[0098] Add 50g water, 5g nano silica, 5g nano wollastonite, 30g micron-sized shell powder (oyster shell powder, which is crushed, enzyme-removed for protein, washed with water, and ball-milled to 5-40 microns) and 1g nano cellulose to a high-speed dispersion vessel, turn on the stirrer, and stir slowly until uniform. Then add 200g of the above self-emulsifying borate ester wax composite water-resistant emulsion, increase the stirring speed, and disperse and grind at high speed for 50 minutes.
[0099] Note: This comparative example does not involve heating to initiate the polymerization reaction; the coating is performed directly.
[0100] III. Preparation of Hydrophobic Paper
[0101] The material obtained above is coated on the surface of the base paper, with the coating amount controlled at 6g / m². The paper is then dried, with the moisture content controlled below 7%, and then hot-pressed for 5 minutes to obtain hydrophobic paper.
[0102] Comparative Example 2 (using insect wax and conventional emulsifiers)
[0103] I. Emulsion Preparation
[0104] Add 95g of insect wax and 9.5g of TW-80 to the emulsification vessel and heat to 80-85℃. Preheat 400g of water to 80-85℃.
[0105] Turn on high shear, increase the speed to 4000-4500 rpm, slowly add a small amount of water, shear and stir for 1 minute, then increase the speed to between 11000-12000 rpm, slowly add the remaining water to the emulsification tank, shear at high speed for 20-30 minutes, and quickly cool to room temperature for later use.
[0106] II. Preparation of Coatings
[0107] Add 50g of water, 5g of nano silica, 5g of nano wollastonite, 30g of micron-sized shell powder and 1g of nano cellulose to a high-speed dispersion vessel, turn on the stirrer, stir slowly until uniform, then add 200g of the above self-emulsifying borate ester wax composite water-resistant emulsion, increase the stirring speed, and disperse and grind at high speed for 60 minutes.
[0108] Note: This comparative example does not involve heating to initiate the polymerization reaction in step (3), but directly performs the coating.
[0109] III. Preparation of Hydrophobic Paper
[0110] The material obtained above is coated on the surface of the base paper, with the coating amount controlled at 6g / m². The paper is then dried, with the moisture content controlled below 7%, and then hot-pressed for 5 minutes to obtain hydrophobic paper.
[0111] Performance testing
[0112] The superhydrophobic paper prepared according to the embodiments and comparative examples of the present invention was subjected to performance testing according to the following methods:
[0113] I. Testing Methods
[0114] Tensile strength: The tensile strength was determined according to GB / T 12914-2018 standard using the constant speed tensile method (tensile speed 20 mm / min), and the tensile strength index was calculated.
[0115] Water contact angle: In accordance with GB / Z 166-2026 standard, the static water contact angle of the paper surface was determined by the static drop method at room temperature using an optical contact angle meter and deionized water as the test solution.
[0116] Water vapor barrier performance: According to GB / T 2679.2-2015 standard, the gravimetric method (permeation cup method) was used to determine the mass of water vapor passing through a unit area of paper within 24 hours under the conditions of temperature 38±1℃ and relative humidity 90±2%RH.
[0117] II. Test Results
[0118]
[0119] As can be seen from Table 1:
[0120] (1) Comparative Example 1 used only borate ester wax (without insect wax and MPS), which could barely achieve a superhydrophobic effect (contact angle 150°), but had a low tensile strength index (30.25 N·m² / g) and poor water vapor blocking performance (460.93 g·m² / g). -2 24h -1 ).
[0121] (2) Comparative Example 2, using only insect wax (without borate ester wax and MPS), failed to achieve superhydrophobicity (contact angle 141°), and had the lowest tensile strength index (28.78 N·m² / g) and the worst water vapor barrier performance (513.66 g·m² / g). -2 24h -1 ).
[0122] (3) Examples 1-3 all achieved superhydrophobic effects (contact angle 155-158°), tensile strength index of 35.24-38.15 N·m² / g, and water vapor blocking performance of 46.07-50.54 g·m² / g. -2 24h -1 All performance characteristics are significantly better than those of Comparative Example 1 and Comparative Example 2. Among them, Example 3 has the best overall performance.
[0123] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A method for preparing a self-emulsifying borate ester wax composite water-resistant emulsion, characterized in that, The method includes the following steps: Insect wax, borate wax and 3-(trimethoxysilyl) propyl methacrylate are mixed, heated to 80-85℃, and water preheated to the same temperature is added. After high-shear emulsification treatment, the mixture is cooled to room temperature to obtain a self-emulsifying borate wax composite water-resistant emulsion. The mass ratio of the insect wax, propyl 3-(trimethoxysilyl)methacrylate, and borate ester wax is (0.1-30):(5-10):(60-95); the mass ratio of water to the total mass of the insect wax, propyl 3-(trimethoxysilyl)methacrylate, and borate ester wax is (2.4-4):
1. The borate ester wax comprises a compound having the following general formula: B(OR1)(OR2)(OR3); R1, R2, and R3 are each independently selected from the following groups: (a)-CH2CH2NH-(CH2CH2O) n -H; (b) -CH2CH(OH)CH2OH or -CH2CH(OCOR x )CH2OCOR y ; (c) -CH2CH(OH)CH3 or -CH2CH(OCOR) z CH3; Among them, R x R y R z Each is independently selected from H or -COC. 25 H 51 ; n = 0.32 - 6.03; and at least one of R1, R2, and R3 is selected from (a), at least one is selected from (b), and at least one is selected from (c); The borate ester wax is prepared by the following method: boric acid, ethylene glycolamine, glycerol, and propylene glycol are reacted in a molar ratio of 1:(0.5-1.5):(0.5-1.5):(0.5-1.5) to obtain a borate ester skeleton; the borate ester skeleton is reacted with wax acid in a molar ratio of 1:(0.5-1.5); ethylene oxide is then added so that the molar ratio of ethylene oxide to the initially added boric acid is (0.5-13):1, and after the reaction, a borate ester wax with an average degree of polymerization n=0.32-6.03 is obtained.
2. The preparation method according to claim 1, characterized in that: The high-shear emulsification process includes: first shearing at 4000-4500 r / min for 1-2 minutes, and then shearing at 11000-12000 r / min for 20-30 minutes.
3. A self-emulsifying borate ester wax composite water-resistant emulsion, characterized in that, Prepared using the method described in claim 1 or 2.
4. A method for preparing a superhydrophobic coating, characterized in that, The method includes the following steps: Water, nano-silica, nano-wollastonite, micron-sized shell powder, nano-cellulose, and the self-emulsifying borate ester wax composite water-resistant emulsion described in claim 3 are mixed, dispersed and ground, heated to 85-90℃, and an initiator solution is added to carry out a polymerization reaction. After the reaction is completed, the mixture is sheared and ultrasonically dispersed to obtain a superhydrophobic coating.
5. The preparation method according to claim 4, characterized in that, The mass ratio of water, nano-silica, nano-wollastonite, micron-sized shell powder, and nano-cellulose is 50:(5-10):(5-10):(30-40):(1-2); wherein, the shell powder is oyster shell powder, which is obtained by crushing, enzymatic removal of protein, washing with water, and ball milling to obtain 5-40 micron shell powder; the mass ratio of the self-emulsifying borate ester wax composite water-resistant emulsion to the total mass ratio of water, nano-silica, nano-wollastonite, micron-sized shell powder, and nano-cellulose is (2-5):
1.
6. The preparation method according to claim 4, characterized in that, The initiator solution is a mixed solution of ammonium persulfate and sodium bisulfite, with a mass ratio of ammonium persulfate to sodium bisulfite of (1-2):(1-2); the total mass concentration of the solute in the initiator solution is 1-5‰; the amount of the initiator solution used, based on the total mass of the solute, is 0.2-0.5% of the mass of propyl 3-(trimethoxysilyl)methacrylate.
7. The preparation method according to claim 4, characterized in that, The dispersion and grinding process takes 50-70 minutes. The polymerization reaction takes 2-4 hours; After the reaction is complete, cool the mixture and perform high shear for 20-40 minutes, followed by ultrasonic dispersion for 5-15 minutes.
8. A superhydrophobic coating, characterized in that, It is prepared by any one of claims 5-7.
9. A superhydrophobic paper, characterized in that, The superhydrophobic coating described in claim 8 is applied to the surface of the base paper, with a coating amount of 6-12 g / m². 2 Dry until the moisture content is below 7%, then hot press for 2-8 minutes to obtain superhydrophobic paper.
Citation Information
Patent Citations
Self-emulsifying alkenyl succinic anhydride sizing agent and preparation method thereof
CN102174780A
Boric acid ester emulsifier for anionic sizing agent as well as preparation method and application of boric acid ester emulsifier
CN117946147A
